Does Ethical Leadership Create Public Value? Empirical Evidences from Banking Sector of Pakistan - Sami, Abdul; Jusoh, Ahmad; Qureshi, Muhammad Imran (International Review of Management and Marketing, 2016)
attention from the public Administrators and researchers. Public value is considered as the contribution of an organization to the society. Citizens pay taxes to the government and in return they demanded benefits, respects and extra care of their rights at public offices. The major focus of researchers is how to create public value. In this article we discuss the role of ethical leadership in creating public value among employees. Leaders of an organization are the key persons who formulate the behavior of their subordinates. With their vision, directives, attitude and behavior they give a direction to their subordinates that how they have to act in that particular organization. Ethical leaders in an organization develop the ethical values in their employees and they always ready to maintain ethical standard of the organization. They consider them as a servant of public and facilitate them beyond their expectation. They feel that they are accountable towards public because they are custodian of public money. These ethical values create public value among the employees and they wholeheartedly devote themselves to fulfill the expectations of public and their customers. We tested our hypothesis on 180 employees of public sector bank in Pakistan. The result of this analysis confirms that ethical leadership is an important phenomenon to create public value among employees. Keywords: Public Value, Ethical Leadership, Public Organization, Public Managers JEL Classification: D73